Penerapan Model Pembelajaran Argument Driven Inquiry terhadap Kemampuan Argumentasi Ilmiah - Putri Qori Utami; Sumari Sumari; I Wayan Dasna (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The purpose of this study is to investigate effect of the Argument Driven Inquiry model on the scientific argumentation skills of 11th grade students in terms of goal orientation. A quasi-experimental research design is a 2 x 2 factorial. The study involved an experimental group (ADI) and a control group (Inquiry) each consisting of 34 students. Two-way analysis of variance (ANOVA) was used for interpreting the data. Based on data analysis, there are differences in students’ scientific argumentation skills between the experimental and control group (sig. 0,011), but there is no significant difference in terms of goal orientation (sig. 0,267). There is no interaction between the learning model and goal orientation on the scientific argumentation skills of students one of the SMAN in Malang (sig. 0,819).Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model Argument Driven Inquiry terhadap kemampuan argumentasi ilmiah siswa kelas 11 yang ditinjau dari orientasi tujuan. Desain penelitian menggunakan rancangan eksperimental semu yaitu faktorial 2 x 2. Penelitian ini melibatkan kelas eksperimen (ADI) dan kelas kontrol (Inkuiri) masing-masing berjumlah 34 siswa. Analisis varian dua arah (Two Way ANOVA) digunakan untuk menginterpretasikan data. Berdasarkan analisis data, terdapat perbedaan kemampuan argumentasi ilmiah siswa antara kelas eksperimen dan kontrol (sig. 0,011), tetapi tidak terdapat perbedaan signifikan ditinjau dari orientasi tujuan (sig. 0,267). Interaksi antara model pembelajaran dan orientasi tujuan tidak ada terhadap kemampuan argumentasi ilmiah siswa salah satu SMAN Malang (sig. 0,819).